Differential diagnosis of Goatpox virus in Taiwan by multiplex polymerase chain reaction assay and high-resolution melt analysis. (March 2014) - Chan, Kun-Wei; Lee, Ming-Liang; Yang, Wei-Cheng; Wong, Min-Liang; Hsu, Wei-Li; Ho, Chia-Fang; Hsieh, Yao-Ching; Wang, Chi-Young
The A32L gene from a Goatpox virus (GTPV) strain isolated from a goat in Yunlin County (Taiwan) displays several substitutions compared with the sequence of the Kenyan GTPV vaccine strain SGP0240 and the Pellor GTPV strain. Samples from the skin lesions on 6 goats with GTPV infection or from goats with Orf virus (ORFV) infection were tested in a multiplex polymerase chain reaction (PCR) system that used primers GPF, GPR1, and GPR2 as well as previously published primers specific for ORFV. These primers were able to amplify either GTPV or ORFV without cross-reactivity. A high-resolution melt analysis (HRMA) was carried out on amplified DNA from the skin lesions of 6 goats with GTPV infection and with the GTPV SGP0240 strain. The results indicated that the melting temperature profiles amplified from samples with Yunlin GTPV infection can be differentiated from the GTPV SGP0240 strain. The findings showed that a successful differential assay for these GTPVs had been developed. Accordingly, both methods can be used to detect and differentiate GTPV isolated from animals that may have either been vaccinated or been infected with a wild strain. The multiplex PCR and HRMA could be used on skin samples of suspected cases to serve as the front-line and confirmative assays, respectively, which will be beneficial to the eradication of GTPV.